Cuidando da comunicação em família: uma reflexão sobre a interação entre cônjuges na Primeira Igreja do Evangelho Quadrangular em Curitiba - Tureck, André (2009)
This research work is the result of ten years of living together with couples who had problems with their marriages, specifically communication problems at the Foursquare Gospel of Church in the city of Curitiba. The increasing of researches about couples who are getting divorced is related with this study, in which the majority of people have a superficial kind of relationship or communication, based on a situation level, not on care and feelings. From this fact come the most different kinds of troubles. The research was separated in three parts. The first part explains the foundation of the Foursquare Gospel of Church in Brazil in 1950, in the city of São Paulo, Cambuci neighborhood and the creation of the Foursquare Estate Couple Ministry (MECQ). The MECQ is formed by priests and independent professionals worried about several problems between couples. Right after, there was a spreading throughout the country, coming to Curitiba, the capital of Parana State. The second part defines the communication process and all other noises that are involved in the communication between people. For instance, couples who deviate the eyes, avoid talking, hit doors, avoid discussing the relationship s problems, who prefer the total silence, who talk through other people, generally the kids. The third part is specifically about demonstrating how the process of rebuilding the relationship happens through dialogs as well as open and effective communication. In other words, the practice, when the couples are invited to participate of classes which are taught in their own houses or at the church, dealing about the marriage as an alliance, the communication inside the family, the care about the children s education, among other measures which are important to support such a special institution as the marriage